Obchody rocznicy Chopina w roku 1910 a integracja narodowa. Chopin a kultura pamięci - Budrewicz, Tadeusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article presents the events of the celebration of Chopin’s 100th birthday in 1910. The article is based on the accounts published in the daily press of the time. The growth of Chopin’s cult in Polish lands culturally connected the nation divided both politically and administratively between three countries (Austria, Prussia and Russia). Despite disruptions by the police that inhibited the organisation of the celebrations in Poznan and Warsaw, the Polish people treated them as a nation-wide occasion and used that time to integrate. The key events were the 50th anniversary of Chopin’s death (1899) and the 100th anniversary of his birthday (1910). The year 1910 was also the 500th anniversary of the Battle of Grunwald which saw the Poles defeat the Germans. Chopin’s year had immense patriotic meaning and integrated the nation living under foreign rule.